Pengaruh Pendayagunaan Zakat Produktif Program Satu Keluarga Satu Sarjana Dalam Meningkatkan Kesejahteraan Mustahik Pada Baznas Kabupaten Kampar - Mairiza, Diany; Widiarsih, Dwi; Winario, Mohd; Rahmawati, Rahmawati; Assyifa, Zubaidah (Journal of Economic, Management, Business, Accounting Sustainability, 2025)
This research aims to measure how much influence the productive zakat utilization of the one poor family one graduate program has in improving the welfare of mustahik at BAZNAS Kampar Regency. The method used was descriptive quantitative with a simple linear regression model Y=a+bX+e, involving 49 respondents as a sample. Data was collected through a questionnaire to obtain data on This can be seen from the results of the T test (partial) with a significance value of 0.001, which is smaller than 0.05, so that the hypothesis H1 is accepted, indicating that there is a positive and significant influence. In addition, the R square value of 0.535 shows that the utilization of productive zakat for one poor family, one graduate program is 53.5% of the welfare level of mustahik, while the rest is influenced by other variables.